Multiple mechanisms for enhanced plasmodesmata density in disparate subtypes of C-4 grasses - Danila, Florence R.; Quick, William Paul; White, Rosemary G.; Kelly, Steven; von Caemmerer, Susanne; Furbank, Robert T. (Oxford University Press, 2018)
Proliferation of plasmodesmata (PD) connections between bundle sheath (BS) and mesophyll (M) cells has been proposed as a key step in the evolution of two-cell C4 photosynthesis; However, a lack of quantitative data has hampered further exploration and validation of this hypothesis. In this study, we quantified leaf anatomical traits associated with metabolite transport in 18 species of BEP and PACMAD grasses encompassing four origins of C4 photosynthesis and all three C4 subtypes (NADP-ME, NAD-ME, and PCK). We demonstrate that C4 leaves have greater PD density between M and BS cells than C3 leaves. We show that this greater PD density is achieved by increasing either the pit field (cluster of PD) area or the number of PD per pit field area. NAD-ME species had greater pit field area per M-BS interface than NADP-ME or PCK species. In contrast, NADP-ME and PCK species had lower pit field area with increased number of PD per pit field area than NAD-ME species. Overall, PD density per M-BS cell interface was greatest in NAD-ME species while PD density in PCK species exhibited the largest variability. Finally, the only other anatomical characteristic that clearly distinguished C4 from C3 species was their greater Sb value, the BS surface area to subtending leaf area ratio. In contrast, BS cell volume was comparable between the C3 and C4 grass species examined.